The Examination of Size Effect and Three Factor Model in Taiwanese Stock Market - Lin, Yu-Sheng (2009)
Financial anomalies in world trading markets have been known about and discussed for several years. The aim of this research is to examine whether or not the size effect—defined simply as the effect of firm size, as measured by market value, on investment returns—could be significantly found in the Taiwanese stock market. In pursuit of this goal, the explanatory powers of the capital asset pricing model (CAPM) (1963) and the Fama and French model (1993) have been applied to this issue. The study period covers the years 1989 to 2008 by using data collected from the Taiwan Economic Journal.